Model Peningkatan Kinerja Karyawan Berbasis Kompetensi, Pelatihan, dan Pengembangan - Bagas Rachmawan; Ruli Haris (Journal Psychology and Economy, 2025)
This study was motivated by the decline in performance of the Agency Development Division at PT Asuransi Sinar Mas during 2022–2024, reflected in lower premium achievement, slower growth of active agents, and decreased policy renewal rates. These gaps are suspected to be linked to internal human resource factors, namely competence, training effectiveness, and employee development programs. The study aims to examine the influence of competence (X₁), training (X₂), and development (X₃) on employee performance (Y). A quantitative approach was applied with saturated sampling, involving 74 respondents, and data were analyzed using multiple linear regression with SPSS version 30. The results show that competence, training, and development each have a positive and significant effect on performance. Simultaneously, the three variables significantly affect performance with a contribution of 57.4%, while 42.6% is explained by other factors outside this study. The findings highlight that strengthening competence, improving training effectiveness, and implementing sustainable development programs can address employee performance gaps. A unique contribution of this research is the evidence that competence is the most dominant factor, reinforcing the view that human resource quality is the key driver of performance in the competitive insurance industry.